Assessment of Single Rejection Band Square Serrated Patch Antenna for Ultra-Wideband Applications (International Journal of Food and Nutritional Sciences, 2021)
This article delves into the design and analysis of a serrated patch antenna featuring a ground slot and microstrip line feed. The study involves a comparative analysis conducted on antennas with five and ten serrated patches positioned at both the top and side edges of the square patch. The entire design process for these iterations is executed using the commercially available HFSS 13 software. To enhance the bandwidth of these antennas, a ground slot has been incorporated into all iterations as a common feature. Subsequently, the return loss and gain characteristics are thoroughly examined and compared across all model variations. Ultimately, the proposed antenna configuration comprises ten serrations positioned along three edges of the square patch. This specific design operates in the ultra-wideband region and exhibits notably high gain compared to the other models. The applications for this antenna encompass WiMAX, WLAN 802.11, LTE 42/43 bands, and it operates within the ultra-wideband frequency range of 3.1GHz to 10.6GHz, with a notable rejection at 5-6GHz.